Management Practices and Development Opportunities for Intensive KUB Chicken Farming in Bengkulu, Indonesia - Nurmeiliasari, Nurmeiliasari (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This study aimed to asses good poultry production practices of intensive native chicken farming and feasibility of development program in Seluma Regency from September to November 2021. A census on 14 native chicken farms in Seluma regency was conducted. The farm’s owners and the poultry men were interviewed for demographic, socio-economic and poultry production practices information.To compare the existing technology with the required Technical Guidelines of KUB chicken farming technology provided by IAARD, data was analyzed using descriptive approaches with qualitative and quantitative methodologies.Farmers, DOC producers, and research team members participated in a focus group discussion (FGD) to discuss the potential for intense native chicken farming (KUB) development in Seluma regency, Bengkulu province. Observation, survey data, and things mentioned in the FGD were used to evaluate KUB's good farming practices. Results showed that KUB farming was conducted by productive young farmers, and the farmers do not rely upon farming only but also other. professions. Housing types applied were stage and cage.  When the chickens reached body weight of 0,8kg  or more, they are sold.  The weekly demand for DOCs is an average of 1,100 chickens, namely 400 KUB chickens and 700 Joper chickens.  Evaluation technology adopted on poultry production revealed that appropriate technology applied to support the farming practices in Seluma regency.